2023
DOI: 10.3390/antibiotics12020379
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bacterial Infections on COVID-19 Patients: Is Timing Important?

Abstract: Background: Along with important factors that worsen the clinical outcome of COVID-19, it has been described that bacterial infections among patients positive for a SARS-CoV-2 infection can play a dramatic role in the disease process. Co-infections or community-acquired infections are recognized within the first 48 h after the admission of patients. Superinfections occur at least 48 h after admission and are considered to contribute to a worse prognosis. Microbiologic parameters differentiate infections that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Several factors can influence the levels of inflammatory parameters, including the hyperinflammatory response, the virulence of microbial agents, COVID-19-induced immunosuppression, the administration of corticosteroids, IL-6 inhibitors such as tocilizumab, etc. [89]. The role of different phenotypes of COVID-19-associated ARDS (CARDS), hyperinflammatory versus hypo/normo-inflammatory, is being discussed too [81].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors can influence the levels of inflammatory parameters, including the hyperinflammatory response, the virulence of microbial agents, COVID-19-induced immunosuppression, the administration of corticosteroids, IL-6 inhibitors such as tocilizumab, etc. [89]. The role of different phenotypes of COVID-19-associated ARDS (CARDS), hyperinflammatory versus hypo/normo-inflammatory, is being discussed too [81].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the notably elevated initial levels of PCT in patients with HAP compared to the bacterial-infection-free cohort, this biomarker exhibits limited predictive capability for superinfection, as the identification of a reasonable cut-off value remains elusive. These observations may be attributed to the administration of corticosteroids and COVID-19-induced immunosuppression [89]. Certain authors argue that PCT values have proven inadequate in confirming bacterial infection, whereas others contend that our understanding in this area remains inconclusive [55,90].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel to the other studies, MR-CoNS (21.5%) was isolated at the highest rate from the blood samples of SARS-CoV-2 patients. In a study by Michailides et al [ 23 ] of patients with COVID-19 infection, CoNS, and K. pneumoniae , together with A. baumannii , were the most frequently isolated bacteria in early and late (> 5 days) nosocomial bacterial infections, respectively. Bahceci et al [ 24 ] isolated CoNS (31%) and A. baumannii (27.5%) at higher rates.…”
Section: Discussionmentioning
confidence: 99%
“…Bahceci et al [ 24 ] isolated CoNS (31%) and A. baumannii (27.5%) at higher rates. Michaelides et al [ 23 ] stated that a prolonged hospital stay may increase CoNS isolation due to the development of superinfections. In the current study, the MR-CoNS (21.5%) and MS-CoNS (9.9%) isolation rates were found to be higher in patients determined to be SARS-CoV-2-positive.…”
Section: Discussionmentioning
confidence: 99%
“…Pierce-Williams et al have not reported any case of maternal death [ 36 ], and therefore, this difference should be taken into consideration seriously and analysed thoroughly, since in the context of this parameter only, earlier initiation of hospitalization seems to be unbeneficial. Moreover, prolonged hospitalization is associated with the increased risk of hospital-acquired infections, especially with the late onset of infection [ 39 ], requiring strict infection control measurements and mandatory microbiological surveillance [ 40 ]. The decedent group of patients had nearly four times the number of prescribed antibiotics compared to the group of survivors, and more importantly, the incidence of nosocomial infections was significantly higher.…”
Section: Discussionmentioning
confidence: 99%